Earth Science Based Investigation of Zsolca Kurgans - Tóth, Csaba Albert; Pethe, Mihály; Prónay, Zsolt; Mcintosh, Richard William; Novák, Tibor József; Molnár, Mihály (JOURNAL OF LANDSCAPE ECOLOGY, 2022)
We aimed to examine the 6 m high, archaeologically unexplored double kurgans rising on the flood-free terrace of Sajó River in the northern part of the Great Hungarian Plain since almost no research had been carried out in relation to these kurgans in the past. If the mounds are studied separately, they belong to the group of the medium, average-sized Hungarian mounds. However, it is no longer ‘average’ in Hungary that two kurgans so close to each other, which are extremely valuable in terms of landscape and plant cover, are still preserved in an intensively transformed cultural landscape. According to the stratigraphic and petrologic analyses, the main building material of the Zsolca kurgans is limestone from the nearby Bükk Mts., rhyolitic tuff mined in Szerencs Hills, topsoil extracted at the foot of the kurgans and yellowish-brown Pleistocene loess sediment mixed with soil. Both mounds are currently surrounded by ring-like depressions not deeper than half a metre, which were originally trenches filled with groundwater nearly three metres deep. The building material of the kurgans was probably extracted from these trenches. Based on the radiocarbon age of the buried paleosols (cal BC 950–404 and cal BC 879–542), it can be stated that the two kurgans may have been built almost at the same time in the 9–6th centuries BC. The double kurgans are identified as Scythian kurgans with a built burial chamber based on geoelectric, radiocarbon and petrologic analyses. According to magnetic anomaly measurements, several Sarmatian graves with circular trenches have been identified in the plain north of the kurgans. This proves that the Zsolca kurgans were important cultic and sacral sites in the centuries AD as well.
Keywords: kurgan; soil and petrological analyses; geophysical analyses; radiocarbon age determination; paleosols; habitat islands